Analisis Kinerja Keuangan Dalam Pengelolaan Alokasi Dana Desa Berdasarkan Rasio Efektivitas dan Rasio Pertumbuhan Selama Pandemi Covid-19 pada Pemerintah Kantor Desa Muangan Kabupaten Sumenep Madura - Devi Irmalasari Assyaffanah; Noor Shodiq Askandar; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Analysis of Financial Performance in Managing Village Fund Allocations Based on Effectiveness Ratio and Growth Ratios during the Covid-19 Pandemic in the Government of the Muangan Village Office, Sumenep Regency. This study aims to understand and analyze good financial performance in managing village fund allocations based on effectiveness ratios and growth ratios at the Muangan Village Office, Sumenep Regency. The type of research used in this research is descriptive quantitative. The data processed is a financial report on village fund allocation in the village income and expenditure budget for the 2018-2021 period. Data collection techniques used in this study were interviews, documentation and observation. The analysis technique used in this study uses the formula: Effectiveness Ratio and Growth Ratio.The results showed that the financial performance of the Muangan Village Government based on the effectiveness ratio was categorized as effective, because the percentage was above 90%, namely 100%. Meanwhile, the ratio of income and spending growth is categorized as low because the percentage is still below 25%. Comparison of financial performance in managing village fund allocations before Covid-19 and when Covid-19 occurred, namely in the decrease in the budget received by villages due to cuts in APBN funds channeled to social and health funds. So that income and expenditure growth decreased when the Covid-19 occurred.Keywords: Financial performance, effectiveness ratio and growth ratio.